New graduate registered nurses' knowledge of patient safety and practice: A literature review. Issue 1 (20th April 2017) - Murray, Melanie; Sundin, Deborah; Cope, Vicki
Abstract : Aims and objectives: To critically appraise available literature and summarise evidence pertaining to the patient safety knowledge and practices of new graduate registered nurses. Background: Responsibility for patient safety should not be limited to the practice of the bedside nurses, rather the responsibility of all in the healthcare system. Previous research identified lapses in safety across the health care, more specifically with new practitioners. Understanding these gaps and what may be employed to counteract them is vital to ensuring patient safety. Design: A focused review of research literature. Methods: The review used key terms and Boolean operators across a 5‐year time frame in CINAHL, Medline, psycINFO and Google Scholar for research articles pertaining to the area of enquiry. Eighty‐four articles met the inclusion criteria, 39 discarded due to irrelevant material and 45 articles were included in the literature review. Results: This review acknowledges that nursing has different stages of knowledge and practice capabilities. A theory‐practice gap for new graduate registered nurses exists, and transition to practice is a key learning period setting new nurses on the path to becoming expert practitioners. Within the literature, there was little to no acknowledgement of patient safety knowledge of the newly registered nurse. Conclusions: Issues raised in the 1970s remain a concern for today's new graduate registered nurses. Research has recognised several factors affecting transition from nursing student to new graduate registered nurse. These factors are leaving new practitioners open to potential errors and risking patient safety. Relevance to clinical practice: Understanding the knowledge of a new graduate registered nurse upon entering clinical practice may assist in organisations providing appropriate clinical and theoretical support to these nurses during their transition.